ANALISIS HUBUNGAN PEMAHAMAN GEOMETRIS DENGAN PENGGUNAAN GEOGEBRA: PERSPEKTIF GURU DALAM PEMBELAJARAN MATEMATIKA - Rahmawati, Parida; Iyam Maryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
His study aims to examine the relationship between students' geometric understanding and the integration of the GeoGebra application from the perspective of educators. Employing a descriptive qualitative approach, data were collected through open-ended questionnaires and interviews with mathematics teachers. The findings indicate that GeoGebra significantly facilitates the visualization of abstract geometric concepts into concrete representations, thereby enhancing student comprehension. Furthermore, the application provides a platform for independent student exploration utilizing its comprehensive features. This habitual independent exploration fosters a more meaningful understanding, which indirectly cultivates students' intrinsic self-confidence. Within this educational context, teachers function as facilitators of exploration and instructional strategists. Nevertheless, several technical constraints hinder the optimal utilization of GeoGebra, including inadequate infrastructure, limited network connectivity, and teachers' unfamiliarity with both the software's advanced features and specific geometric content. Consequently, this study recommends continuous professional development for educators and the design of instructional modules tailored to optimize GeoGebra as an effective and meaningful learning medium. Keywords: Geometric Understanding; GeoGebra; Teacher's Role;